Playing with confidence: The relationship between imagery use and self-confidence and self-efficacy in youth soccer players - Munroe-Chandler, K.; Hall, C.; Fishburne, G. (Journal of Sports Sciences, 2008)
Confidence has been one of the most consistent factors in distinguishing the successful from the unsuccessful athletes (Gould, Weiss, & Weinberg, 1981) and Bandura (1997) proposed that imagery is one way to enhance confidence. Therefore, the purpose of the present study was to examine the relationship between imagery use and confidence in soccer (football) players. The participants included 122 male and female soccer athletes ages 11-14 years participating in both house/recreation (n = 72) and travel/competitive (n = 50) levels. Athletes completed three questionnaires; one measuring the frequency of imagery use, one assessing generalised self-confidence, and one assessing self-efficacy in soccer. A series of regression analyses found that Motivational General-Mastery (MG-M) imagery was a signifant predictor of self-confidence and self-efficacy in both recreational and competitive youth soccer players. More specifically, MG-M imagery accounted for between 40 and 57% of the variance for both self-confidence and self-efficacy with two other functions (MG-A and MS) contributing marginally in the self-confidence regression for recreational athletes. These findings suggest that if a youth athlete, regardless of competitive level, wants to increase his/her self-confidence or self-efficacy through the use of imagery, the MG-M function should be emphasised.